(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the development of language in the context of rapidly advancing computer and internet technologies. The study demonstrates that digital technologies play a crucial role in shaping modern language and continuously contribute to the expansion of users’ vocabulary according to their level of engagement with digital environments. In particular, younger generations, despite possessing strong English language skills, are frequently unfamiliar with business-related slang, while older people often struggle to understand youth slang formed within entertainment and online cultures. The practical value of this research lies in its relevance for philologists and specialists in digital technologies who are interested in improving communication through the integration of computer- and internet-based lexical units into everyday speech.